Analysis of Grammatical Errors in the Use of Complex Sentences Among EFL University Students - Nurdin Nurdin; Wiwit Sariasih; Darmawati Darmawati (Indonesian Journal of Multidisciplinary on Social and Technology, 2026)
Producing complex sentences is an important part of academic writing and effective communication in English. But many English as a Foreign Language (EFL) learners struggle repeatedly with grammar when they are trying to construct complex sentences. The present study aims at investigating the grammatical errors in the use of complex sentences of undergraduate students in English Literature and the factors leading to these errors. The study employed a qualitative case study design with 30 participants, including one English lecturer and 29 undergraduate students taking an academic writing course. The data were gathered from students’ written assignments, semi-structured interviews with the lecturer and selected students and classroom observations. Thematic analysis was used to analyze the collected data to identify the recurring patterns of grammatical errors and the factors influencing students’ performance. The results revealed a number of primary types of grammatical errors in the production of complex sentences. These included misapplication of subordinate conjunctions, errors in subject–verb agreement, inconsistency of tense, sentence fragments, run-on sentences, omission of vital grammatical components, and incorrect construction of a relative clause. Thematic analysis also showed four main themes for these mistakes: limited competence in grammar, influence of L1, limited practice on complex sentence construction, and problems in applying grammar knowledge in the context of academic writing task. The study concludes that the grammatical errors in the construction of complex sentences are caused not only by the lack of knowledge of English grammar, but also the difficulty of transferring the explicit knowledge of grammar to communicative writing practice. The results highlight the significance of integrating explicit grammar teaching with contextualized writing tasks, continuous formative feedback and collaborative learning approaches to improve students’ grammatical accuracy. Keywords: grammatical mistakes, complex sentences, English Literature students, qualitative methodology, thematic analysis, academic writing